The Quality of Frozen Semen with Different Thawing Duration and Temperature on Simmental Bull - Nisa, Dhinda Choirun; Susilawati, Trinil; Yekti, Aulia Puspita Anugra; Rachmawati, Achadiah (Faculty of Animal Science, Universitas Brawijaya, 2022)
This study aimed to determine the accuracy of various thawing duration and temperatures to the quality of Simmental bull frozen semen. The experimental design used was a randomized group design with five treatments and ten replications, then analyzed using Chi-Square to compare the expected percentage of motility is 40%, and total motile spermatozoa are 10 million/straw value of SNI. A further test is carried out with Duncan's Multiple Range Test (DMRT) if there is a difference. The thawing treatments were 30 seconds at 37ËšC water temperatures (T0) according to SNI and at 15 seconds (T1), 30 seconds (T2), 45 seconds (T3), and 60 seconds (T4) with 28ËšC tap water temperatures. Variables observed involve motility, viability, abnormalities, concentration, and total motile spermatozoa. The data were analyzed using Analysis of Variance (ANOVA) with a significant difference in variance (P<0,05). The results showed that the different duration and temperatures of thawing influence motility (P<0,05) and the total motile spermatozoa, while the viability, abnormalities, and concentration had no influence (P>0,05). The motility and the total motile spermatozoa reach the highest results at the tap water temperatures T3 (P<0,05), while the lowest results were in T1 (P<0,05). It can be concluded that the different duration and temperatures of thawing influence motility and total motile spermatozoa. The best quality of Simmental bull frozen semen can be obtained with thawing using tap water at 28â„ƒ temperatures for 45 seconds.